Selection of project managers: An overview - Marija Šiško Kuliš (Business Systems Research (BSR), 2020)
Background: The project manager choice is one of the most important, complicated and multi-layered decisions in project management. Although the competence of a project manager is the subject of numerous studies, mostly in the field of economic sciences, there are still relatively few studies dealing with project manager selection. Objectives: The aim of this paper is to provide a useful overview of research on approaches, models, techniques, and competencies during the process of selecting project managers, in order to improve understanding an effective process of selecting project managers from academic researchers and practitioners' point of view. Methods/Approach: This article is a scientific review of previously published studies that are linked to competencies of a project manager and the process of project manager selection according to the traditional and the modern approach. Results: The process of selecting project managers is not sufficiently investigated in Croatia, while most of the research is focused to traditional approach. Conclusions: In this work, we propose a combination of the traditional and the modern approach to the selection of project managers, which would be based on the multicriteria decision making.
Keywords: L21; M21; M54; 330; manager; project; approach; competence; model; criterion